Forms of Resistance: Uses of Memoir, Theory, and Fiction in Trans Life Writing. Issue 3 (3rd July 2017) - Jacques, Juliet
ABSTRACT: This article examines the forms of writing that transgender (hereafter 'trans') people in North America, the United Kingdom and Australia have used to convey their experiences to a wider public, since the first sex reassignment surgeries were performed during the inter-war period. I will discuss how transsexual people first used memoir to counter sensationalistic mass media coverage, and then how feminist critiques of their works led to 'post-transsexual' theory, which deconstructed the conventions and clichés that the transition memoir genre had developed. These theorists suggested new ways to document gender-variant lives beyond a generalised desire for public acceptance and in response to social concerns: the policies of the gender identity clinics, who decided who could access medical services, and on what terms, especially the demand that patients 'pass' in their acquired genders and hide their histories; and the exclusion of trans people from feminist spaces, and gay/lesbian politics. The article concludes with a consideration of my own autobiographical writing, in a newspaper blog and a memoir, and how my practice responded to and attempted to change how trans people were expected to write about their lives.